Resilience and its association with religiosity, spirituality and affective disorders in dialysis chronic kidney patients (Research, Society and Development, 2021)
Objectives: to evaluate the state of resilience and investigate its association with religiosity/spirituality and affective disorders in dialysis. Methods: Single-center, cross-sectional study with patients aged ≥ 18 years, dialysis time ≥ 6 months. The research instruments were the Resilience Scale-14 items; DUREL Scale; Daily Spiritual Experience Scale (DSES); and Anxiety, depression and stress scale (EADS). The state of resilience was assessed and its association tested with the patients'religiosity, spirituality, anxiety-stress-depression state. Results: 58 patients were included, 55.2% male, mean age 51.5 years. Resilience was very low /low/lower limit in 15.5%, moderate in 31%, moderately high/high in 50% of patients. A significant difference in the depression, anxiety, stress and intrinsic religiosity scores was detected according to resilience, with higher scores in patients with lower resilience. Resilience had a moderate negative correlation with the score of RI (r = -0.407; p = 0.002), anxiety (r = -0.360; p = 0.006) and depression (r = -0.316; p = 0.016) and weak negative correlation with DSES (r = -0.281; p = 0.034). There was no association with age, marital status, economic or cultural level, type of religion or laboratory tests on dialysis. Conclusion: Resilience was moderately high/high in 50% of dialysis’patients, and the higher the level of resilience, the more positive affective state, the better the full experience of religiosity and the greater frequency in spiritual experiences with God. Interventions that can assist in the management of difficulties and adaptations to chronic kidney disease should be promoted.